Internationalisms and the politics and policies of mission in the Portuguese colonial empire (1885-1930) - Jerónimo, Miguel Bandeira (2017)
This article addresses the politics and the policies of mission in the Portuguese colonial empire in the late nineteenth and early twentieth centuries. It explores the extent to which such policies were shaped by the international, transnational, and inter-imperial dynamics of political and religious internationalisms embraced by sectors of the Catholic and Protestant churches.